Labor Division in Pig Farming Households: An Analysis of Gender and Economic Perspectives in the Red River Delta Vietnam - Ninh, Nguyen Thi Hai; Lebailly, Philippe; Dung, Nguyen Mau (International Journal of Economics and Financial Issues, 2019)
This paper attemps to understand about gender division of labor in pig farming households and to identify factors affecting that division. Using primary data collected from 40 pig farming, we find that female laborers play more important role in pig production. More than 60% of women participating in making decision regarding to many stages of pig farming. Especially, in small scale households women are observed to take main responsibility for almost all activities as many men do off-farm jobs far from home. Compared to wives, husbands are more likely to make decision regarding pig farming. Nevertheless, in households with higher-educated and younger couples, we identify a higher probability of husband and wife making decision together. Therefore, to improve the role of women in pig farming, it is necessary for local authority to train them knowledge relating to pig farming and to change their husbands’ perception on gender equality. Keywords: Labor Division, Pig farming household, Gender and Economic Perspective JEL Classifications: C01, J01, J16 DOI: https://doi.org/10.32479/ijefi.7274